Histopathological evaluation of chromoblastomycosis: A literature review (Research, Society and Development, 2021)
Chromoblastomycosis (CBM) is a cutaneous or subcutaneous mycoses. The trauma occurs when the fungus is installed and is more prevalent in individuals living in tropical and subtropical regions, with earliest descriptions dating back to 1920. The diagnosis of CBM is based on the incidence of cases in the endemic areas and is commonly reached through microbiological analyses to identify the etiologic agent in clinical samples. The process for the analysis of the collected samples allows one to visualise the muriform cells, which are brown, rounded structures having crossed chambers and that can be commonly called sclerotic bodies, characterising the positive diagnosis. The objective of this review was to verify the connection of the histopathological techniques to the diagnosis of CBM.